The Effect of Ocean Loading on the Growth of Basaltic Ocean Island Volcanoes and Their Magmatic Plumbing System - Le Corvec, Nicolas; McGovern, Patrick J. (Frontiers in Earth Science, 2018)
Basaltic shield volcanoes most commonly form as intraplate volcanic ocean islands that arise from the ocean floor and continue to grow above the sea water level to form gigantic volcanic edifices. The volcanic edifice evolution and the internal stress distribution may be influenced by the water load of the surrounding ocean. We therefore investigate how the presence of an ocean affects the internal stress of a volcanic edifice and thus magma propagation by means of axisymmetric elastic models of a volcanic edifice overlying an elastic lithosphere. We designed a volcanic edifice featuring a height of ~6,000 m and a radius of ~ 60 km which was build up either instantaneously or incrementally, i.e., by emplacing new layers of equal volumes on top of each other. The latter was done in a way that the resulting stress and edifice geometry from one step served as the initial condition of the subsequent step. Thus, each new deposit was emplaced on an already deformed and stressed model layer. The ocean load was simulated using a boundary condition at the surface of the model. For the instantaneous volcano growth scenario, different water levels were investigated, while for the incrementally growing volcano the water level was fixed to 4,000 m. We employed both half-space and flexural models and compared the deformation of the volcanic edifice, as well as its internal stress orientation and magnitude with and without applying an ocean load. Our results show major differences in the resulting state of stress between an instantaneous and an incrementally built volcanic edifice. Furthermore, we show that the presence of an ocean decreases the amount of flexural response due to the buoyancy effect, which in turn decreases the magnitude of differential stress within the models. Also, our results imply that the stress orientation and the type of potential magma intrusions within the volcano as well are influenced by the loading effect of an ocean. Our results therefore provide new insights into the state of stress and deformation within the edifices of basaltic ocean island volcanoes with significant implications for magma ascent and eruption and edifice construction.